Campaigning for president 2012 : strategy and tactics - Johnson, Dennis W., 1943- (Routledge, Taylor & Francis Group, 2014)
"In this important and timely volume, Dennis W. Johnson has assembled an outstanding team of political scientists and political professionals to examine one of the fiercest and most closely fought presidential elections of our time"--Resumé vydavatele
Keywords: 2012; 2001-2010; prezidenti -- Spojené státy americké -- 2001-2010; volební kampaň -- Spojené státy americké -- 2001-2010; prezidentské volby -- Spojené státy americké -- 2001-2010; politická kampaň -- Spojené státy americké -- 2001-2010; presidents -- United States -- 2001-2010; election campaign -- United States -- 2001-2010; presidential elections -- United States -- 2001-2010; political campaigns -- United States -- 2001-2010; Spojené státy americké -- politika a vláda -- 2001-2010; United States -- politics and government -- 2001-2010; kolektivní monografie; collective monographs